The possible therapeutic role of curcumin and quercetin in the early-stage of COVID-19—Results from a pragmatic randomized clinical trial - Ujjan, Ikram Din; Khan, Saeed; Nigar, Roohi; Ahmed, Hammad; Ahmad, Sagheer; Khan, Amjad (Frontiers in Nutrition, 2023)
Curcumin (CUR) and quercetin (QUE), two natural polyphenols, are common components of human nutrition, possess broad-spectrum antiviral, antioxidant and immunomodulatory biological activities. Both curcumin and quercetin have recently shown inhibition of SARS-CoV-2 in invitro assays. In the present study we investigated the possible adjuvant effect of curcumin and quercetin combined supplementation (CUR-QUE) along with standard of care for mild to moderately symptomatic COVID-19 outpatients in a pragmatic, open-label, randomized controlled clinical trial, conducted at Liaquat University of Medical and Health Sciences, Jamshoro, PK. Patients were randomized in a 1:1 ratio into two treatment arms i.e; standard of care alone (n=25, control group) or CUR-QUE supplementation with standard of care (n=25, CUR-QUE group). The CUR-QUE adjuvant therapy consisted of a daily intake of 168 mg curcumin and 260 mg quercetin as two soft capsules twice a day for 14 days. At completion of one-week of treatment, most of the patients in the CUR-QUE group showed an expedited clearance of the viral infection i.e; 18 (72.0%) vs 6 (24.0%) patients in the control group, tested negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the reverse transcription-polymerase chain reaction (RT-PCR) oropharyngeal swab test, p = 0.0002, showing a statistically significant difference in the viral clearance in the two groups. COVID-19-associated acute symptoms were also speedily resolved in the CUR-QUE treated patients i.e; 10 (40.0%) vs 4 (16.0%) patients in the control group, p = 0.061. The adjuvant CUR-QUE supplementation therapy was well-tolerated by all 25 patients and no treatment-emergent effects or serious adverse events were reported. The results revealed in this exploratory study suggest possible therapeutic role of curcumin and quercetin supplements against SARS-CoV-2 including inhibitory activity against the viral replication and could possibly help in the speedy recovery of early-stage mild to moderate symptoms of COVID-19. The suppression of SARS-CoV-2 observed in this study, possibly due to the synergistic pharmacological effects of curcumin and quercetin, is likely due to the inhibition of 3C-like protease as reported in the in vitro assays. Further research is warranted.